2017
DOI: 10.1063/1.4995284
|View full text |Cite|
|
Sign up to set email alerts
|

Near-infrared measurement of water temperature near a 1-mm-diameter magnetic sphere and its heat generation rate under induction heating

Abstract: This paper presents a method of measuring the temperature of water near a 1-mm-diameter magnetic sphere under induction heating. The method is based on the temperature dependence of the absorption coefficient of water at a wavelength of 1150 nm. In this study, two-dimensional images of the absorbance, which is the transverse projection of the absorption coefficient of water, were acquired by a near-infrared camera through a telecentric lens, and three-dimensional radial profiles of the temperature were then ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The NIR absorption technique is based on the principle of temperature dependence of the absorption bands of water in the NIR region. As is shown in Figure 1a, the ν 1 + ν 2 + ν 3 absorption band of water is observed in the 1100-nm to 1250-nm wavelength (λ) range and shifts to shorter wavelengths as the temperature increases 19 . Here, ν 1 + ν 2 + ν 3 means that this band corresponds to the combination of the three fundamental O-H vibration modes: symmetric stretching (ν 1 ), bending (ν 2 ), and antisymmetric stretching (ν 3 ) 20,21 .…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The NIR absorption technique is based on the principle of temperature dependence of the absorption bands of water in the NIR region. As is shown in Figure 1a, the ν 1 + ν 2 + ν 3 absorption band of water is observed in the 1100-nm to 1250-nm wavelength (λ) range and shifts to shorter wavelengths as the temperature increases 19 . Here, ν 1 + ν 2 + ν 3 means that this band corresponds to the combination of the three fundamental O-H vibration modes: symmetric stretching (ν 1 ), bending (ν 2 ), and antisymmetric stretching (ν 3 ) 20,21 .…”
Section: Introductionmentioning
confidence: 86%
“…Alternatively, the surface temperatures of media have been remotely measured via infrared radiation thermometers to estimate the inner temperatures 14 . However, when a medium containing a small heat source is a water layer or a non-turbid aqueous medium, we have demonstrated that a near-infrared (NIR) absorption technique is useful to measure the temperatures 15,16,17,18,19 . This paper presents the detailed protocol of this technique and representative results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption bands of water and ice in the NIR had been reported as 760, 970 (or 980), 1190, 1450, and 1940 nm for liquid water and 1030 nm for water ice [35,36]. The water and ice absorbance in the NIR range increases or the peak wavelengths shift with a temperature increase, but the change is relatively small in the wavelength region between 750 and 1000 nm [37][38][39]. The absorption properties of water result from the vibration transition in H 2 O, involving various harmonics and combinations-induced asymmetric and symmetric stretch and bending mode transition by H-O-H [40].…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents a near-infrared (NIR) imaging system that simultaneously measures the temperature and flow fields formed by a 1-mm-diameter steel sphere. The temperature is based on the temperature dependence of an NIR absorption band of water [2,3], Using this NIR-based technique with the Inverse Abel Transform (IAT) [4], we got absorbance difference images of water around the steel sphere and then estimated the temperature distribution. The flow visualization and velocity measurement are implemented by particle tracking velocimetry (PTV) [5].…”
Section: Introductionmentioning
confidence: 99%